KLF2 inhibits TGF-β-mediated cancer cell motility in hepatocellular carcinoma. (21st April 2020) - Li, Yining; Tu, Shuo; Zeng, Yi; Zhang, Cheng; Deng, Tian; Luo, Weicheng; Lian, Lingyan; Chen, Ling; Xiong, Xiangyang; Yan, Xiaohua
Abstract: Feedback regulation plays a pivotal role in determining the intensity and duration of TGF-β signaling and subsequently affecting the pathophysiological roles of TGF-β, including those in liver malignancy. KLF2, a member of the Krüppel-like factor (KLF) family transcription factors, has been implicated in impeding hepatocellular carcinoma (HCC) development. However, the underlying molecular mechanisms are not fully understood. In the present study, we found that TGF-β stimulates the expression of KLF2 gene in several HCC cell lines. KLF2 protein is able to inhibit TGF-β/Smad signaling in HCC cells as assessed by luciferase reporter assay. Further studies indicated that KLF2 inhibits the transcriptional activity of Smad2/3 and Smad4 and ameliorates TGF-β-induced target gene expression, therefore creating a novel negative feedback loop in TGF-β signaling. Functionally, stably expression of KLF2 in HCCLM3 cells attenuated TGF-β-induced cancer cell motility in wound-healing and transwell assays by interfering with TGF-β-mediated upregulation of MMP2 . Together, our results revealed that KLF2 protein has a tumor-suppressive function in HCC through a negative feedback loop over TGF-β signaling.